PENGARUH NILAI KOEFISIEN AERODINAMIKA DAN PADA KESTABILAN TERBANG GERAK PERIODE PENDEK (SHORT PERIOD) RKX-200 LAPAN [EFFECT OF AERODYNAMICS COEFFICIENT VALUE AND TO THE STABILITY OF THE FLY MOTION SHORT PERIOD RKX-200 LAPAN] - GS, Endang Mugia (Indonesian Journal of Aerospace, 2012)
The rocket flew of short period modes of motion, can be used as a way to measure the stability of the rocket flying. By performing simulation using software Missile DATCOM obtained aerodynamic coefficient and , each of which affects the value of the natural frequency and damping motion short period. RKX-200 Lapan rocket is a quite stable rocket. And the magnitude of the aerodynamic coefficient : -0,12 to -.0,02 and value of : -2,4 to -1,2, with each value remains negative at cruising speed prediction of 0,1 M s.d 2,0 M. It’s good enough to be the guided missile with value 0,18  SM  0,46.